Electron Emitter Tip-Shape Effects on the Electron Beam Trajectory in a Microcolumn - Chul Kim, Young; Joon Ahn, Seung; Kim, Dae-Wook; Kweon Jang, Won; Seob Kim, Ho (Asian Journal of Chemistry, 2012)
One of the most significant parameter for the electron beam properties of a microcolumn is the electron emitter tip shape. The electron tip shape in a microcolumn is one of the most effective factors to the behaviour of electron beam. We investigated the tip shape effect on the electron beam trajectory. To investigate the tip shape effect on electron beam properties, we analyzed the electrostatic potential and field strength inside the microcolumn and also electron beam trajectories. The divergence angle at the different tip apex such as flatted tip-shape, facetted tip-shaped, rounded shaped and triangle-shaped also discussed.